The Effect of Training and Work Environment on Work Motivation through Organizational Commitment as an Intervening Variable for Employees of PT Yamaha Musical Products Indonesia - Maulidha Kurnia Dini; Sriyono Sriyono (International Consortium of Education and Culture Research Studies, 2021)
This study aims to examine the effect of Training and Work Environment on Work Motivation with Organizational Commitment as an Intervening Variable on the employees of PT Yamaha Musical Products Indonesia. The research method used is quantitative with path analysis research techniques and using research instruments in the form of questionnaires. The results show that training affects organizational commitment, work environment influences organizational commitment, training influences work motivation, work environment influences work motivation, organizational commitment affects work motivation. The path analysis result show that organizational commitment can’t be an intervening variable for training on work motivation and organizational commitment can be a partial mediation for work environment on work motivation. Furthermore, PT YMPI in Pasuruan Regency remains consistent to increase work motivation through training and work environment. Although organizational commitment provides a low increase, it is necessary that to further enhance the organizational commitment that can strengthen the work motivation so that it can improve company’s performance in the face up to business competition